PENERAPAN METODE SINGLE EXPONENTIAL SMOOTHING DALAM MEMPREDIKSI JUMLAH PENERIMAAN MAHASISWA BARU - Maktisen Ena (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Forecasting is a technique for estimating future data by looking at past data and current data. Admissions of new students at Tribuana Kalabahi University are carried out every year since the founding of the Tribuana Kalabahi University campus, in 2007, the number of new student admissions from year to year has experienced an upward trend, therefore forecasting is carried out using Single Exponential Smoothing. The amount of data from 2007 to 2022 is 16 data. The calculation results with Single Exponential Smnothing have the lowest MAPE value, namely 1.41005% with a value of α = 0.1, the number of new student admissions is 664 people